2017
DOI: 10.5812/ijcm.9052
|View full text |Cite
|
Sign up to set email alerts
|

Rare Presentation of Pancreatic Cancer: A Case Report

Abstract: Introduction: Hypercoagulable state may be an important first presentation in malignancies especially pancreatic cancer. The trousseau syndrome is caused by venous thrombosis, non-bacterial thrombotic endocarditis and arterial thrombosis. We describe a patient who had the cerebral infarction as the initial manifestation of pancreatic cancer and we discuss that full work up for every patient with atypical stroke should be done. Case Presentation: We report a 67-year-old man who developed multiple cerebral infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The mortality rate among patients with meningeal TB in this study was 17.4%, and the loss to follow-up rate was 8.3%, which was higher than other types of EPTB. Other studies from the United States, Iran, and Pakistan have also reported meningeal TB as a significant risk factor for unfavorable treatment outcomes [4,40,41].…”
Section: Discussionmentioning
confidence: 94%
“…The mortality rate among patients with meningeal TB in this study was 17.4%, and the loss to follow-up rate was 8.3%, which was higher than other types of EPTB. Other studies from the United States, Iran, and Pakistan have also reported meningeal TB as a significant risk factor for unfavorable treatment outcomes [4,40,41].…”
Section: Discussionmentioning
confidence: 94%
“…Whole-body positron emission tomography followed by CT abdomen confirmed the presence of pancreatic cancer. Most pancreatic malignancies are invasive ductal carcinomas that infiltrate adjacent organs [ 15 ]. It is rarely diagnosed in its early stages, and as a result, it is mostly incurable in the majority of instances [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most pancreatic malignancies are invasive ductal carcinomas that infiltrate adjacent organs [ 15 ]. It is rarely diagnosed in its early stages, and as a result, it is mostly incurable in the majority of instances [ 15 ]. The initial step in treating Trousseau's condition is to remove the underlying tumor, although this is not always feasible because the tumor is frequently unresectable [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vein of Labbe, also known as the inferior anastomotic vein, is one of the cortical veins that anastomoses between the middle cerebral vein and transverse sinus and drains the lateral temporal lobe’s blood [ 3 ]. Risk factors for cerebral vein thrombosis include trauma, inherited and acquired thrombophilia, malignancy, exogenous hormones and pregnancy [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%